A preliminary study of the genes related to aggression and insensitivity to pain in autism spectrum disorders - Elif Funda Sener; Mustafa Caglar Sahin; Serpil Taheri; Keziban Korkmaz Bayramov; Mert Kahraman Marasli; Gokmen Zararsiz; Mehmet Canpolat; Nilfer Sahin; Didem Behice Oztop (Psychiatry and Clinical Psychopharmacology, 2017)
Objective: Autism spectrum disorders (ASDs) is a heterogeneous neuropsychiatric disorder with widespread abnormalities of social interaction and communication, showing severely restricted interests and extreme repetitive behavior. The relationship between aggressive behavior, insensitivity to pain, and ASDs could not be explained completely. Therefore, we aimed to contribute to the etiology by examining the gene expressions of OPRL1, TACR1, and HTR1E in patients with ASDs. Methods: This study was held in the Genome and Stem Cell Research Center of Erciyes University. In this present study, the expressions of OPRL1, TACR1, and HTR1E genes were studied in 22 ASD patients and 14 healthy controls. Quantitative Real-time Polymerase Chain Reaction (qRT-PCR) was used for gene expression studies. Results: There was a statistically significant difference in terms of the expression of the three genes, which we examined between the ASD patient and control groups. Positive and strong correlations were obtained between the three gene expressions in the ASD group and this finding was found to be statistically significant. Conclusions: Considering all these findings, large-scale and new researches are needed for revealing the roles of genes and their pathways which are related to aggression and insensitivity to pain in ASDs. Our results will lead to new research studies in this field.